EUPHEMISM IN DAVID CAMERON’S POLITICAL SPEECH IN ISIS ATTACKS - Nuzulianda Ferina Purba; Meisuri Meisuri; Syamsul Bahri (LINGUISTICA, 2017)
This study deals with euphemism in political speech of David Cameron about ISIS attacks. The objectives of the study were to find out the types of euphemsim used in DavidCameron’s speech on ISIS attacks and the reason why the most dominant types was choosen. The study was conducted by applying descriptive qualitative method.The data for this study were David Cameron political speech transcript in 20 July 2015, 14 November 2015, 2 December 2015, 5 february 2016. The source of the data was from United Kingdom govermentwebsite .The data were analyzedusing the theory of Allan and Burridge (1991). The findings of the study showed that the types of euphemism used in David Camerons political speech about ISIS attacks were: figurative expression(28,8%) ,circomlocution (15,5%), ommision (13,3%), ommision (13,3%) , hyperbole (11,1%), understatement (8,8%) ,flippancy(8,8%), abbreviation (8,8%),  borrowing (2,2%) and clipping (2,2%)  . Figurative expression as the most dominant type used by David Cameron because it make words in speech more organized as a nice thing to be spoken in public in order to convince people.Keywords: euphemism, euphemism types, speech, politic